The Role of Professional Behavior to Improve Patient Safety Culture in Clinical Nurses: A Cross-Sectional Study - Mirhosseini , Seyedmohammad; Basirinezhad , Mohammad Hasan; Ebrahimi , Hossein (Shahroud Journal of Medical Sciences, 2021)
Background: Safety culture is one of the most important determinants of patient safety in hospitals. Due to the increasing prevalence of medical errors, increasing public attention, and public opinion pressure on this issue as well as the limitations of studies in this area, the current study was conducted to identify the role of professional behavior to improve patient safety culture in clinical nurses.Methods: This cross-sectional study was performed on 230 nurses in Shahroud Iran. Data collection instruments included a demographic information form, the Hospital Survey on Patient Safety Culture questionnaire, and the Nursing Professional Behaviors Scale. Stratified random sampling was used and data were analyzed by using descriptive and inferential statistics (linear regression analysis).Results: Participants’ mean scores of patient safety culture and professional behavior were 132.51 ±15.97 and 109.57±18.01, respectively. A high score of nurses' professional behavior was directly associated with a higher level of patient safety culture. In addition, the number of working hours per week and change in the workplace were significantly related to patient safety culture level (Pvalue=0.002).Conclusions: Professional behavior is an effective factor in enhancing safety culture in nurses. Therefore, paying attention to the training and proper application of professional behavior in nurses can improve the level of patient safety culture.Keywords: Nurse, Patient safety, Professional behavior